Young Entrepreneurs' Financial Compass: How Attitudes, Norms, and Self-Efficacy Direct Financial Intentions and Actions - Ramadhan Harahap; Sri Rahayu; Maudy Lestari (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
This study investigates the impact of financial attitude, subjective norms, and financial self-efficacy on the financial behavioral intentions of young entrepreneurs. As young entrepreneurs face increasing pressure to make strategic financial decisions, understanding the factors influencing their financial behavior is crucial. The primary goal of this research is to evaluate how financial attitudes, subjective norms, and self-efficacy in financial management shape young entrepreneurs' intentions to engage in prudent financial behaviors. A quantitative, cross-sectional survey will be conducted, targeting young entrepreneurs actively running their own businesses. Data will be collected through in-person surveys distributed at entrepreneurship events, business incubators, and local business networks. The analysis will utilize Partial Least Squares Structural Equation Modeling (PLS-SEM) to explore the relationships among the variables. The study anticipates finding that positive financial attitudes, influential subjective norms, and high financial self-efficacy significantly impact financial behavioral intentions. These results are expected to provide valuable insights into the determinants of financial decision-making among young entrepreneurs. The research will contribute to enhancing financial education programs and offer practical recommendations for interventions aimed at strengthening financial self-efficacy and attitudes, ultimately promoting more responsible financial behaviors.